INERTIAL DIRECTIONS BUILDER WITH DUAL AUTOCOMPENSATION OF INFLUENCE OF EXTERNAL INTERFERENCE - Мельник, Виктория Николаевна; Карачун, Владимир Владимирович (Eastern-European Journal of Enterprise Technologies, 2010)
The analytical structure of pointer of direction is built on the base of triaxial astatic gyroscope with twochannel autoindemnification of influence of external noises. The correlation for determination of девиации of ax of figure in the first two approaching was gotten.